Vallens övervintring i norra Finland - Jamalainen, E. A. (Agricultural and Food Science, 1970)
This discussion, with some additions by way of completion, is based upon a paper read by the author in Sollefteå, Sweden, Aug. 14th 1969, where Norwegian, Swedish and Finnish experts discussed some problems relating to agriculture in North Scandinavia. On the basis of research and experiments carried out at plant breeding institutes, local agricultural experimental stations and the Department of Plant Pathology, it has been possible to establish that extensive damage due to low temperature parasitic fungi is not encountered regularly in South or Central Finland. In certain years, however, Fusarium nivale (Fr.) Ces., Typhula ishikariensis Imai (syn. T. idahoensis Remsb.) and T. incarnata Lasch ex Fr. may appear as a cause of injury, even in the Southern parts of the country. Sclerotinia borealis Bub. & Vleugel occasionally causes losses in Central Finland. In Central and South Finland the Scandinavian varieties of timothy (Phleum pratense), meadow fescue (Festuca pratensis) and meadow grass (Poa pratensis) are, as in corresponding conditions elsewhere in Scandinavia, comparatively resistant to low temperature parasitic fungi. Cocksfoot (Dactylis glomerata) is more susceptible to these fungi than the former grasses, as is perennial rye-grass (Lolium perenne) also in South Finland. Overwintering damage to ley grasses in North Finland. Significant results on the overwintering of ley grasses in North Finland have been obtained at the Arctic Circle Agricultural Experimental Station at Apukka, near Rovaniemi. The director of this station, Dr. A. Isotalo, has during several successive springs carried out visual analyses of the damage caused by low temperature parasitic fungi in ley grass trials, which have been run on both peat bog and mineral soils. Table 1 presents data on the damage by F. nivale, S. borealis and T. ishikariensis to a plant stand of timothy, meadow fescue and cocksfoot, according to visual assessments. The plant stand usually recovers during the growing season, so that the economic losses are less than the spring assessments might indicate. Information about the overwintering capacity of ley grasses in North Finland has also been obtained on journeys made from the Dept, of Plant Pathology into Lapland. Damage caused by S. borealis varies greatly from winter to winter. There have been years in which the fungus has been comparatively rare, whereas in other years the damage caused to timothy and other ley grasses has been very extensive. In the winter season 1960—61 S. borealis caused particularly severe injury in North Finland (cf. Fig. 1), and in the overwintering season 1965—66 the damage was on the same scale. In the spring of 1966, at the Arctic Circle Agric. Exp. Sta. at Apukka, this fungus caused almost complete failure in the comparative experiments between the different ley grasses. S. borealis is adapted to low-temperature conditions. In experiments made at the Dept. of Plant Pathology, the mycelia of this fungus grew relatively rapidly at 0 .. +5° C, while at + 15° C their growth was weak. The fungus causes the greatest damage when the autumn is damp and chilly, the snow cover thick and the ground only slightly frozen, and also in the spring if the snow melts slowly. During the spring of 1969, damage by low temperature parasitic fungi in Lapland was very extensive, about 50 % of 1st-year timothy being destroyed in several districts. Older stands of the grass had escaped fungal injury to a greater degree. In the overwintering season 1968—69, T. ishikariensis was the chief cause of damage in South and Central Lapland (Fig. 2). Further north, F. nivale replaced it with increasing freguency. During this season S. borealis caused only local damage. Extensive damage by low temperature parasitic fungi does not in fact occur year by year in North Finland, but in winters that are favourable for the fungi, S. borealis and T. ishikariensis, and in part also F. nivale, may cause even total losses of the leys. In some years S. borealis, in others T. ishikariensis, are the causes of the largest amounts of damage. Under these circumstances, low temperature parasitic fungi are factors which, when they appear, make the cultivation of ley grasses uncertain under northern conditions. In certain years water injuries may occur on grasses grown on peat soils in North Finland. As the snow-cover is formed early and melts late, greater injury from frost does not generally occur in the north. If the ground is still bare late in the autumn or early in the spring, frost damage may appear. Information concerning the resistance of ley grasses to low temperature parasitic fungi has been obtained at the Arctic Circle Agric. Exp. Sta. at Apukka, during trials of ley grass varieties carried out over a number of years. Mainly Finnish and Swedish varieties were used in these experiments. In addition, a few varieties from Denmark, Germany and Canada were tried. Damage by low temperature parasitic fungi to timothy varied greatly from year to year, and depending on the age of the grass stands. First year leys proved to be the most susceptible to overwintering injury. Damage to varieties of meadow fescue by low temperature parasitic fungi was of the same order as to varieties of timothy. Overwintering damage to varieties of cocksfoot by these fungi was greater than to either timothy or meadow fescue. Varieties of perennial ryegrass were, practically speaking, incapable of overwintering at Apukka, on account of fungal damage. Since the beginning of 1966, experiments have been carried out to study in Finland the resistance to low temperature parasitic fungi of the varieties and lines of ley grasses obtained from plant breeding institutes in other Scandinavian countries. The experiments were made at the Arctic Circle Agric. Exp. Sta. at Apukka (Fig. 3) and also later at the Central Finland Agric. Exp. Sta. at Kuusa. In order to realise this joint Scandinavian project, financial support has been provided by state scientific commissions from Denmark, Finland, Norway and Sweden. A three metre wide border within the experimental plots was treated with 50 % quintozene or PCNB (pentachloronitrobenzene), applied at the rate of 10 kg/ha in late autumn. This measure facilitated the estimation of biotic and abiotic damage to the plant stands in the experiments. In these trials, which had been made on peat soil, severe injury by water occurred during the winter season 1966—67. In the spring of 1968, S. borealis appeared in great abundance and caused damage to timothy, meadow fescue and cocksfoot. In the winter season 1968—69, T. ishikariensis almost completely destroyed all the varieties and lines of grasses in the trials. In the trials run over the overwintering season 1967—68, the residual effect of the PCNB in cocksfoot was comparatively small. Considerable frost damage also occurred in this grass. Four Norwegian varieties and lines of meadow-grass were included in these trials. Three lines were badly damaged by S. borealis, as were two varieties of common bent-grass which were included in the trial (Table 2). At the Central Finland Agric. Exp. Sta. at Kuusa, a joint Scandinavian overwintering experiment with perennial ryegrass was carried out on both fine sand and silt soil (Table 3). Damage by F. nivale, T. ishikariensis and S. borealis was found to have occurred within the plant stand. Among the various varieties used, the Swedish variety Valinge overwintered best. The residual effect of the PCNB application made in the autumn of 1967 was quite small. On the basis of the experiments described above, it is not possible to draw any long-term conclusions regarding the relative susceptibilities to low temperature parasitic fungi of varieties of timothy, meadow fescue, cocksfoot, or other ley grasses. The varieties of ley grasses cultivated in North Finland at present are among the most resistant of all existing varieties to low temperature parasitic fungi. Nevertheless, even these varieties are very susceptible to attack when conditions are favourable for the appearance of the fungi. The plant breeder will certainly still be called upon to do a lot more work in breeding varieties more resistant to these parasites in northern part of Scandinavia than we have at present. PCNB (quitozene) application to low temperature parasitic fungi. In the trials made at the Arctic Circle Agric. Exp. Sta. with timothy and meadow fescue, to stands of which PCNB preparation (50 %, 10 kg/ha) had been applied during the autumn before the snow came, the application gave satisfactory control of low temperature parasitic fungi in several cases. During the winter season 1967—68, at several sites in Lapland, trials were made in which this substance was applied to plant stands. In several of these experiments, the use of PCNB gave excellent, or at least satisfactory control of low temperature parasitic fungi. The degree of effectiveness of PCNB in controlling S. borealis, on Scandinavian plant breeding material at Apukka 1967—68 (Table 2), was quite high in several cases. The application, however, was not sufficiently large to protect adequately those varieties which were particularly susceptible to these fungi. By means of an application of quintozene to first year grass leys, it was possible to establish that the residual effect in yield increases also during later years. The significance of nitrogen in the overwintering of grasses. In 1967, the Agric. Res. Centre took up the study of the significance of nitrogen in increasing the protein content of ley grasses under cultivation. For this purpose, experiments were established with different ley grasses at the Dept. of Plant Husbandry, and at local experimental stations in various parts of the country. The nitrogen applications were 150, 300, 450 and 600 kg/ha of nitrogen in the form of nitrate (Oulu Saltptre, 26 % N). One might have expected that the abundant quantities of nitrogen would, have promoted damage by F. nivale. However, that this was not the case could be established with some degree of certainly. In the nitrogen fertilizer trials made at the Arctic Circle Agric. Exp. Sta. at Apukka during the winter season 1967—68 and earlier (Fig. 1) extensive damage due to S. borealis appeared in timothy, in the plots to which no nitrogen had been applied. On the other hand, stands of timothy supplied with abundant quantities of nitrogen remained free of fungus damage. In this case, nitrogen increased the resistance of timothy to S. borealis. As opposed to this, large applications of nitrogen were injurious as regards overwintering in the experiments made in 1968—69. At the Häme Agric. Exp. Sta. at Pälkäne in Central Finland (Fig. 4), the Karelia Agric. Exp. Sta. at Anjala East Finland, and at the Dept. of Plant Husbandry at Tikkurila, near Helsinki, large quantities of applied nitrogen resulted in complete or nearly complete destruction of timothy and meadow fescue. In these instances no evidence of damage by low temperature parasitic fungi was found. The stands which had received large amounts of nitrogen were destroyed. It is likely that plants which have received large quantities of nitrogen lose their reserves of sugar during the winter, resulting in a weakened overwintering capacity. Factors as yet unknown may also enter into the picture.